2013
DOI: 10.1016/j.ophtha.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Efficacy and Safety of 0.5 mg or 2.0 mg Ranibizumab in Patients with Subfoveal Neovascular Age-related Macular Degeneration

Abstract: Proprietary or commercial disclosure may be found after the references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
366
2
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(397 citation statements)
references
References 18 publications
17
366
2
12
Order By: Relevance
“…The 'observe-and-plan' regimen allows for elimination of monthly repeated evaluation visits during the treatment plans, thereby reducing the number of ophthalmic assessments to one-third (33%) and one-fourth (24%) during the first and second year, respectively, as compared with the monthly visits required in PRN regimens. 11,12,16 Thus far, various Figure 3 Distribution of the first measured interval after loading doses (horizontal axis), plotted against the last applied interval at month 24 (vertical axis), for all eyes that underwent treatment with ranibizumab for neovascular age-related macular degeneration according to the studied regimen 'observe and plan'. The term 'observation' is equivalent to any interval longer than 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'observe-and-plan' regimen allows for elimination of monthly repeated evaluation visits during the treatment plans, thereby reducing the number of ophthalmic assessments to one-third (33%) and one-fourth (24%) during the first and second year, respectively, as compared with the monthly visits required in PRN regimens. 11,12,16 Thus far, various Figure 3 Distribution of the first measured interval after loading doses (horizontal axis), plotted against the last applied interval at month 24 (vertical axis), for all eyes that underwent treatment with ranibizumab for neovascular age-related macular degeneration according to the studied regimen 'observe and plan'. The term 'observation' is equivalent to any interval longer than 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Simply reducing the intravitreal injections to a fixed retreatment every 3 months was significantly inferior to monthly injections and resulted in the loss of initial visual acuity (VA) improvement. [8][9][10] Although the individually adjusted pro re nata (PRN) retreatment regimen was able to reduce the number of retreatments with (near) noninferiority of visual results as compared with monthly retreatment, 11,12 this regimen still requires monthly monitoring visits to detect disease recurrence and determine the need for retreatment. In a context of chronic care management and indefinite treatment duration, monthly monitoring visits place a heavy burden on ophthalmic institutions, with new patients being regularly added because of the high incidence of nAMD.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The HABOR Study reported equivalent visual and anatomical outcomes between high dose (2.0 mg) and conventional dose (0.5 mg) of ranibizumab for treatment of exudative AMD at 12 months. 12 Stratification of lesion subtypes was not a part of these studies; therefore, its applicability to the more difficult-to-treat subtypes of neovascular AMD such as vPED is unknown. Recent studies evaluated the outcomes of ranibizumab for treating vPED due to AMD, but not comparing the results of various doses of ranibizumab.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies evaluated the outcomes of ranibizumab for treating vPED due to AMD, but not comparing the results of various doses of ranibizumab. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Our prospective study addressed the benefits and risks of 2.0 vs 0.5 mg ranibizumab for treating vPED due to AMD on a monthly as well as pro-re nata (PRN) basis for up to 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, doubling the dose has not been proven to increase the efficacy of ranibizumab in in the treatment of both age related macular degeneration and diabetic macular edema. 26,27 The READ-3 compared between 0.5 mg and 2.0 mg ranibizumab in the treatment of diabetic macular edema and found that after 6 months visual gains in the 0.5 mg group were higher (+9.43 letters) than the 2.0 mg group (+7.01 letters; P = 0.161). 28 In addition, the RISE/RIDE study found no significant difference between monthly 0.3 mg and the 0.5 mg dose of ranibizumab after 24 months of treatment.…”
Section: Drcr Protocol T-1 and 2-year Datamentioning
confidence: 99%